Analisis Kebutuhan Media Pembelajaran Interaktif pada Materi Statistika SMP Kelas VIII - Aisyah Three Hapsari; Hendra Kartika; Muthiah Fildzah Noverli (FKIP Universitas Mataram, 2026)
The utilization of interactive learning media in statistics instruction remains suboptimal, whilestudents demonstrate an increasing need for more engaging technology-based learning. Thiscondition emphasizes the importance of needs analysis as a foundation for developing relevantlearning media. This study aims to analyze and identify the needs for interactive learning mediain statistics for eighth-grade junior high school students. This research is a descriptive studyemploying a qualitative approach. The subjects consisted of two mathematics teachers and eightstudents from eighth-grade selected purposively with heterogeneous academic abilities. Datacollection was conducted through semi-structured interviews. The data were analyzed using theMiles, Huberman, and Saldaña model, encompassing data reduction, data display, and conclusiondrawing. The findings concluded that teachers and students require interactive learning mediawith specific characteristics to address students' learning difficulties in understanding statisticalconcepts. The identified media needs were categorized into three main aspects, including graduallystructured content presentation accompanied by real-world examples and dynamic visualizationsusing images or animations; two-way interactivity through quizzes or games coupled with practiceexercises featuring immediate feedback; and visually appealing yet simple design with flexibleaccessibility via smartphones. Therefore, the development of interactive learning media with suchcharacteristics is highly necessary to support more effective, interactive, and meaningful statisticslearning for eighth-grade junior high school students.